Strategi Madrasah Dalam Mengembangkan Program Kelas Tahfidz Al-Qur’an - Siti Nur Asiyah (THE JOER: Journal Of Education Research, 2023)
The purpose of publishing this article is to describe the development strategy for the tahfidz Al-Qur'an class program at MTsN 3 Mojokerto in terms of planning, implementation, and valuation. This research belongs to the type of qualitative research, qualitative research in which all the data used cannot be measured with definite numbers but places more emphasis on meaning. This research is a type of field research because the researcher is present directly in the field or research location, namely Madrasah Tsanawiyah Negeri 3 Mojokerto, the following stages will be explained: (a) Basic objectives for developing the tahfidz al-Qur'an class program, (b) Determining content or material tahfidz al-qur'an class program at Madrasah Tsanawiyah Negeri 3 Mojokerto, (c) Using lesson time allocation, (d) making learning planning tools. At the implementation stage of the Tahfidzul Qur'an Program includes preliminary activities, core activities and closing activities. At the evaluation stage of the development of the tahfidz class program through 5 evaluation stages, namely: formative evaluation, summative evaluation, context evaluation, input evaluation and process evaluation.